Pharmaceuticals in the environment - Hester, R. E. (Ronald E.); Harrison, Roy M., 1948- (Cambridge : Royal Society of Chemistry, 2016)
'Medicines play an important role in the treatment and prevention of disease in humans and animals, but residues from these medicines can be released into the environment through a number of routes during their manufacture, use and disposal. It is only recently that the potential environmental impacts of this exposure to pharmaceuticals are being considered. The book explores where pharmaceutical residues can be found, e.g. in surface waters, drinking water, sediments and the marine environment; the sources of these residues, from manufacture through to disposal of unused medicines; how these residues break down; and how this all impacts on wildlife and human health. In reviewing the current position and examining further possible impacts, this book is an important reference for researchers working in the pharmaceutical industry, as well as for environmentalists, policy makers and students on pharmacy and environmental science courses wanting to better understand the impacts of pharmaceuticals on the environment.'--
Note continued: 2. Legal and Regulatory Demands Concerning Environmental Impact of VMPs in the EU -- 3. The Impact of VMPs on the Environment -- 3.1. Emission of VMP Residues Related to Production -- 3.2. Emission of VMPs Residues Related to Use -- 3.3. Emission of VMPs Residues Related to Disposal -- 4. Specific Toxic Effects of VMPs -- 4.1. Antiparasitics in the Aquatic Environment -- 4.2. Antimicrobials in Aquatic and Terrestrial Environments -- 4.3. Antiparasitics for Pasture Animals -- 4.4. Risks to Vultures and other Necrophagous Bird Populations in the European Union in Connection with the Use of Veterinary Medicines Containing Diclofenac -- 5. Monitoring and Ecopharmacovigilance -- References.
Includes bibliographical references and index.
Keywords: Drugs -- Environmental aspects; Pharmaceutical chemistry